Inter- municipal cooperation and costs: expectations and evidence - Bel, Germa; Warner, Mildred E. (2015)
Austerity and fiscal crisis make the search for cost-saving reforms in local government more critical. While cost savings from privatization have frequently proven ephemeral, inter-municipal cooperation has been a relatively understudied reform. We analyse the literature on cost savings under cooperation and find that savings are dependent on (1) the cost structure of public services, particularly those related to scale and density economies and externalities, (2) the structure of local government (size, metropolitan location, powers granted by the nation or regional state), and (3) the governance framework at the local/regional level where cooperation varies from informal to formal. European studies give more emphasis to cost savings, while US studies focus on coordination concerns arising from the higher degree of devolution in the US local government system. - Reproduced.
Keywords: Local government